INFLAMMATION INDEXES AS PREDICTORS OF RECURRENCE IN PATIENTS WITH SURGICALLY RESECTED NON-SMALL CELL LUNG CANCER - Оlga Smorodska; Yuliia Moskalenko; Мykola Kononenko; Stanislav Ivanov (Eastern Ukrainian Medical Journal, 2022)
Introduction. Prediction of lung cancer recurrence is one of the most urgent problems of modern oncology. Scientists are trying to find independent predictors that will help intensify, personalize the patient’s treatment, and prevent the disease relapse on time. The study aimed to find indicators of inflammation that could be independent predictors of disease recurrence in patients with surgically resected non-small cell lung cancer. Materials and methods. The study was conducted retrospectively. The study group included 104 patients with non-small cell lung cancer who received surgical treatment and adjuvant chemotherapy or chemoradiotherapy from 2014 to 2018 at the Sumy Regional Clinical Oncology Dispensary. Based on the results of the blood count tests, the inflammation indices were calculated before chemotherapy or chemoradiotherapy and one month after their completion. Systemic inflammatory response index (SIRI), systemic inflammatory index (SII), neutrophil/lymphocyte ratio (NLR), platelets/lymphocytes ratio (PLR), lymphocyte/monocyte ratio (LMR), monocyte/lymphocyte ratio (MLR) were calculated. Using ROC analysis, cut-off points were found. Cox regression was used to find independent predictors of lung cancer recurrence. Results. During the observation period, relapse of the disease was recorded in 42 (40.4%) patients. The average recurrence-free survival was 56.3 months, range of 4–84.0 months (95% CI = 46.866–65.683). Before chemo- or chemoradiation therapy, the cut-off points for NLR1, PLR1, MLR1, LMR1, SII1, and SIRI1 were 1.80, 126.35, 0.22, 4.80, 521.22 and 0.96, respectively. Cut-off points for NLR2, PLR2, MLR2, LMR2, SII2, and SIRI2 at stage one month after completing courses of chemotherapy or chemoradiotherapy were 1.33, 153.80, 0.26, 3.98, 450.10 and 0.82 respectively. According to ROC analysis, only PLR1, SII1, LMR1, and LMR2 indices are reliable and can be used in further Cox regression analysis. Univariant Cox regression showed that LMR1 and SII1 were significantly associated with disease recurrence. Multivariate Cox regression identified SII1 as the only independent predictor of disease recurrence. Conclusions. Among numerous inflammation indices as an independent predictor for disease recurrence in non-small cell lung cancer patients who received surgical treatment and chemotherapy or chemoradiotherapy, only systemic inflammation index (SII1) at the stage before chemotherapy or chemoradiotherapy can be used. Indicators above 521.22 could be a predictor of high-risk recurrence of lung cancer.